If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3b=b+28
We move all terms to the left:
3b-(b+28)=0
We get rid of parentheses
3b-b-28=0
We add all the numbers together, and all the variables
2b-28=0
We move all terms containing b to the left, all other terms to the right
2b=28
b=28/2
b=14
| 19m=–17+20m | | 5(g-8)=13 | | 2c=7c-40 | | 12t/12=-36/12 | | -6=k/3 | | c/2+9=30 | | -40=q/5+-36 | | x^2=217 | | 10/n=4/10 | | 2x-30=95 | | y+75/2=8 | | -n/12=12/6 | | f(-10)=-10^2+2(-10)-10 | | 12-10=14t+2 | | s-93/2=3 | | F(x)=13-7x | | m/9=11/3 | | (2x+4/5)=6 | | 8t+80=12t | | 3(-5y-4)-2y=-29 | | Y=-101x | | 60q+11=-13 | | 16x^2+12.8x+3.2=0 | | 3y+13+4y+5=123 | | 2.5=45n=18 | | x^2=505 | | x+5.8=7.39 | | 12t=-8t+80 | | 24=2a+10 | | -6q+21=-63 | | 5(3c2)-7c=40-2c | | 4+8q=60 |